Age-Related Quality of Life in Cardiac Surgical Patients with Extracorporeal Life Support - Terrazas, Jesús A.; Stadlbauer, Andrea C.; Li, Jing; Bitzinger, Diane; Diez, Claudius; Schmid, Christof; Camboni, Daniele (The Thoracic and Cardiovascular Surgeon, 2024)
Background The rationale of the study was to analyze the impact of age on quality of life (QoL) in patients who had undergone cardiac surgery with consecutive extracorporeal life support (ECLS) treatment.Methods The study population consisted of 200 patients, operated upon between August 2006 and December 2018. The patient cohort was divided into two groups following an arbitrary cutoff age of 70 years. Comparative outcome analysis was calculated utilizing the European Quality of Life-5-Dimensions-5-Level Version (EQ-5D-5L).Results A total of 113 patients were 70 years or less old (group young), whereas 87 patients were older than 70 years (group old). In 45.7% of cases, the ECLS system was established during cardiogenic shock and external cardiac massage. The overall survival-to-discharge was 31.5% (n = 63), with a significantly better survival in the younger patient group (young = 38.9%; old = 21.8%, p = 0.01). Forty-two patients (66%) responded to the QoL survey after a median follow-up of 4.3 years. Older patients reported more problems with mobility (y = 52%; o = 88%, p = 0.02) and self-care (y = 24%; o = 76%, p = 0.01). However, the patients' self-rated health status utilizing the Visual Analogue Scale revealed no differences (y = 70% [50–80%]; o = 70% [60–80%], p = 0.38). Likewise, the comparison with an age-adjusted German reference population revealed similar QoL indices. There were no statistically significant differences in the EQ-5D-5L index values related to sex, number of comorbidities, and emergency procedures.Conclusion Despite the limited sample size due to the high mortality rate especially in elderly, the present study suggests that QoL of elderly patients surviving ECLS treatment is almost comparable to younger patients.
Keywords: quality of life; geriatric (includes elderly); extracorporeal membrane oxygenation; ECMO